Building collaboration through action research: the case of Ottotomo Forest Reserve in Cameroon - Gonsalves, Julian Francis (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2013)
A research that uses a series of Participatory Action Research (PAR) tools to identify specific management problems, attempts to analyse those problems and establishes collaborative arrangements for future management inputs into the Ottotomo Forest Reserve in the Central Province of Cameroon, one of the protected areas in the country where several management strategies have been tested with varying degrees of success (e.g., the Tropical Shelterwood System (TSS) silvicultural technique was piloted in this forest more than 30 years ago).